Efficiency Analysis of Central Government Transfer Funds to the Regions Income Inequality - Noviar, Helmi; Syahril, Syahril; Badli, Saiful; Sari, Yunidar Purnama (Universitas Teuku Umar, 2023)
The government spending budget in the form of transfers to the regions is the government's effort to reduce income inequality in every region in Indonesia. Therefore, this study aims to analyze income inequality through the government budget to regions, including transfers of balancing funds and transfers of special autonomy funds and adjustments using the estimated Gini Ratio. This study uses secondary data from 2007 to 2020 sourced from the Ministry of Finance of the Republic of Indonesia and the Indonesian Central Bureau of Statistics. The analysis results show that the estimated transfer allocation of funds to the regions for income inequality has not been efficient, with a technical efficiency ratio of an average of 0.95 of the potential budget spent with realization based on estimates frontier regression line. This means there is inefficiency in the government budget in the form of transfers to urban and rural areas. This proves that the government's efforts in transfers to the regions have not been fully efficient in reducing income inequality in the area. The policy needed is to focus on capacity-building programs and human resources who will manage funds in the regions and act as a driving force for development.